PELAKSANAAN ALUR PELAYANAN PASIEN DAN KLAIM DENGAN SISTEM JAMINAN SOSIAL NASIONAL (SJSN) 2014 DI INSTALASI REKAM MEDIS RUMAH SAKIT UMUM PKU MUHAMMADIYAH BANTUL - , LAILATUL AZIZAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: To apply BPJS program, the health institutions, especially hospitals must show their quality in providing good service and exact to the consumer that is based on standards of professionalism, which is expected to fulfill the expectations of the people (consumers). At PKU Muhammadiyah Bantul General Hospital, particularly at medical record installation not perform BPJS preparation optimally and service provided will be less than the maximum. So how far it must be the extent to which the implementation is carried out so as to show the quality in providing good service and exact to the consumer. Objective: To determine flow implementation of patient service and claim with the National Social Security System (SJSN) 2014 at Medical Record Installation General Hospital PKU Muhammadiyah Bantul. Methods: This type of research is a descriptive study with a qualitative approach with a cross-sectional study design. The subjects in this research were the head of the medical record, medical record officers, insurance officers, relation officer, coder, physicians, nurse, BPJS verifier. Objects in this research is the implementation flow of the patient service, file medical records as one of the requirements of the insurance claim, work instructions used in connection charging medical record file, work instructions related to the implementation of Social Security, and the implementation of a medical record document management as supporting documents smoothness patients claim National Social Security System 2014. Mechanical Data collection by observation, interviews, and documentation studies. Results: The results of this research indicate that the implementation of patient service are in accordance with the rules, but there are still misconceptions about the flow of patient service related to the collection of patient files and information assurance requirements regarding working hours counter guarantee. Lack of work instructions regarding a flow of BPJS claim because the rules of BPJS flow still changed makes the medical record officers insufficiently know about what the continuation BPJS claim process. Necessary requirements related to claim BPJS, there are still patients who do not carry the full requirements and health workers who have not been filled with a complete medical record file. Additionally PKU Muhammadiyah Bantul General Hospital have not revised the work instructions of registration and coding implementation, then LAN network that often trouble or errors.